PERAN DAN KONTRIBUSI PUSTAKAWAN SEBAGAI MITRA RISET - Muhammad Tawwaf (UIN Imam Bonjol Padang, 2020)
This paper tries to explore the contribution and experience as a librarian to conduct research in various countries with different themes. The purpose of this study was to determine the ability and professionalism of librarians as research partners in helping researchers conduct research. The methodology used in this research is descriptive analysis which takes two locations (countries) where the research is Japan and the Netherlands. The Sources of data used as population and object of research are the results of interviews, observations and sources of references from the results of searching for library information used by researchers. The results of this study are to provide an overview of the ability of librarians to search for information to know and find sources of information in various media both books, scientific journals, and other online media that support lecturer research as research partners who are needed. The practice of collaborating with librarians in certain fields will demonstrate the competence and role of librarians who are very strategic in the success of a research program. Equally important is the recognition of research partners and the contribution of librarians to a study. Research collaboration between lecturers and librarians as research partners will increase the number of research publications in journals of national and international repute and good communication between lecturers and librarians.